Removal of Ag(I) from Aqueous Solutions by Thiol-ene-Based Hydrogel and Its Application to Radiographic Films - KÖK YETİMOĞLU, ECE; KAHRAMAN, MEMET VEZİR (SPRINGER, 2014)
The thiol-ene-based P(Penta3MP4/PEGDA/AAc) hydrogels were prepared by UV curing technique, then characterized and used as adsorbents for the investigation of the effect of process parameters such as pH of solution, contact time, and initial concentration of solution, on the removal of Ag(I) from aqueous solution. The results indicate that the adsorption of Ag(I) ions from aqueous solutions is strongly dependent on pH under experimental conditions. Both Langmuir and Freundlich isotherm models were applied to experimental data, and the results show that the adsorption process is well fitted to the Langmuir isotherm model. Selectivity, reusability, and applicability of hydrogels to radiographic film waste were investigated.
Keywords: Adsorption; Thiol-ene; Silver; Radiographic film waste; CHELATING RESINS; FACILE SYNTHESIS; SILVER RECOVERY; METAL-IONS; ADSORPTION; MICROPARTICLES; GOLD(III); SORPTION; CEMENTATION; CHITOSAN